Mekanisme Hukum Adat Perdmaian (Mela Sare) Dalam Mewujudkan Rekonsiliasi Para Pihak Pasca Putusan Pengadilan Pada Masyarakat Lamaholot Di Adonara – Flores Timur - Sili, Handrianus David Ola (Jurnal Hukum & Pembangunan, 2022)
The substance aspect that underlies this writing in the Adonara community, the implication of a court decision is the breakdown of relations / relations both personal and social between the parties to the dispute or "kenetun". In order for the implication of the court decision to help eliminate the "kenetun" customary bulkhead, an effort was made to reconcile the parties to the dispute. Interesting to study more deeply, the Lamaholot community has a customary law tradition that is packaged in the traditional ritual of peace mela sare. This research is sociological law (sociological legal research) or empirical legal research with the type of research on legal effectiveness. Based on the results of the research that has been carried out, it can be found that several aspects that bind the customary law of peace (mela sare) in realizing the relations of the parties after the judicial decision is diantranya: First, resolve salihan. Secondly, save the traditional adat block. Third, value oriented namely; the value of justice, the value of truth, the value of peace. Fourth, build relationships and victims. While for legal renewal is restorative justice. The aim of restorative justice is to restore harmony between victims and murder. For victims, this means physical loss and psychological loss. For the brave, it means taking responsibility, taking shame and regaining dignity.